Nurse educator confidence in clinical teaching in Vietnam: A cross-sectional study. Issue 3 (June 2018) - Nguyen, Van N.B.; Duke, Maxine; Forbes, Helen
Abstract: Background: There have been shortages of qualified nurses to teach nursing in Vietnam, leading to the involvement of physicians to undertake nurse educator roles for decades. Aim: To explore (i) how Vietnamese clinical nurse educators are recruited for their roles, (ii) their perceived confidence in clinical teaching and (iii), the association between perceived confidence and nursing background. Methods: Descriptive survey design was used to conduct the study. Cross-sectional surveys were used to collect data from 334 clinical nurse educators from 19 institutions in Vietnam. Findings: Clinical nurse educators in Vietnam were recruited from three sources: (1) new Bachelor of Nursing graduates, (2) experienced nurses or nurse educators and (3) those who did not have a background in nursing (mostly physicians). Regardless of the professional background participants perceived their confidence in clinical teaching at moderate and high levels. Experienced nurses rated their confidence lower than all other groups, including those who did not have any clinical nursing experience prior to commencing the clinical educator role. Discussions: The recruitment of non-nurses and nurses without experience as clinicians to undertake the role of nurse educator role does not appear to affect their confidence in clinical teaching. The professional backgrounds of these groups appear to be unique to Asian contexts and may provide insight into identified delays in the development of professional identity in nursing students. Conclusions: This study has contributed important insights into the current situation surrounding nursing education in Vietnam. Recommendations are provided to inform future recruitment of clinical nurse educators.